Structural Stability Analysis of Multistory Building Structure under Wind Load Conditions (International Journal of Innovative Research in Engineering & Management, 2023)
In the current research the effect of wind  load on structural stability of building structure is evaluate  using techniques of Computational Fluid Dynamics. The  CFD analysis on building is conducted using ANSYS  simulation package. The FSI simulations considered the  complex interactions between the structural components  and the surrounding fluid flow, providing valuable insights  into the structural response and its vulnerability to external  loading conditions. Through a combination of  computational tools and numerical methods, the study was  able to accurately predict the structural response, including  deformations, stresses, and critical failure points.
Keywords: CFD; Building load; Wind Load